The first phone call from heaven [compact disc, unabridged] : a novel - Albom, Mitch, 1958- (HarperAudio, 2013)
The story of a small town on Lake Michigan that gets worldwide attention when its citizens start receiving phone calls from the afterlife. Is it the greatest miracle ever or a massive hoax? Sully Harding, a grief-stricken single father, is determined to find out.